Compressive stress-strain relationships of concrete exposed to elevated temperatures based on mesoscopic damage method. (September 2022) - Bai, Wei-Feng; Wang, Wei-Li; Guan, Jun-Feng; Wang, Jian-you; Yuan, Chen-yang
Damage evolution in concrete after high temperature is a complicated procedure, in which the pre-peak strain hardening behaviour, the post-peak strain softening behaviour and the impact of high temperature play key roles. Uniaxial and biaxial compression damage models of concrete considering high temperature degradation effect are proposed based on damage theory and experimental phenomena. They consider that the destruction of concrete is actually the cumulative evolution course of the two meso-damage modes, rupture and yield. High temperature changes the mechanical performance in microstructure of concrete and the generation and propagation of microcracks. It could be described by adjusting the probability distributions which characterize the mesoscopic damage evolution. The damage constitutive model is employed to determine the stress-strain behaviour of concrete under uniaxial compression, and the calculated results are compared with the experimental results under different high temperature levels. Results indicate that the proposed model can not only predict the stress-strain behaviour with acceptable accuracy in macroscopic scale, but also reveal the damage evolution mechanism in mesoscopic scale. Finally, the constitutive behaviour under biaxial compression is also simulated to investigate the influence of high temperature on biaxial stress-strain behavior and strength envelope.